Spatial Performativity/Spatial Performance - Smitheram, Jan (Architectural theory review, 2011)
This paper considers Judith Butler's exploration of the symbolic and iterative relations of gender and the extension of her ideas into architectural discourse. The paper is set out in two main parts. The first introduces Butler's notion of performativity, in particular looking at how space operates in her text. The second part of the paper looks critically at how her work has been explored by architectural scholars; highlighted in this section is the translation of Butler's work into architecture through the lens of performance. This paper concludes by arguing that a synthesis between performance and performativity opens up a more nuanced theorisation of a subject who acts in space and time.